Śākta sampradāya tenā siddhānto, Gujarātamāṃ teno pracāra, ane Gujarātī sāhitya ūpara asara - Mehta, Narmadashankar Devshankar (SAMP early 20th-century Indian books project, 1932)
On Shaktism, its history and development in Gujarat, and its impact on Gujarati literature.